Phosphorus-containing polymer as well as preparation method and application thereof

Through the gradual polymerization method of radical addition, phosphorus-containing polymers containing P-C bonds were prepared using α,ω-non-conjugated diene monomers and hypophosphoric acid or hypophosphite compounds, which solved the preparation in the prior art Due to the cumbersome method and the harsh reaction conditions, the efficient preparation of phosphorus-containing polymers with improved performance is achieved.

CN119431804AActive Publication Date: 2025-02-14NANJING UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310973699.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14
Estimated Expiration
2043-08-04

AI Technical Summary

Technical Problem

In the prior art, the preparation method of phosphorus-containing polymer based on P-C bonds has problems such as cumbersome preparation, harsh polymerization conditions or safety hazards.

Method used

Use α,ω-nonconjugated diene functional monomers and hypophosphoric acid or hypophosphite compounds such as diallyl oligosil, diallyl piperazine, diallyl ether and octadiene. Phosphorus-containing polymers containing P-C bonds were prepared by stepwise polymerization through radical addition.

Benefits of technology

Under mild reaction conditions, it is possible to efficiently prepare phosphorus-containing polymers with improved performance for the preparation of functional materials such as lithium salt composite polyelectrolytes, polyphosphonate surfactants and flame retardants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431804A_ABST
    Figure CN119431804A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus-containing polymer and a preparation method and application thereof, the phosphorus-containing polymer comprises a repeating unit derived from an alpha, omega-non-conjugated diene monomer and a repeating unit derived from a phosphorus source monomer, the alpha, omega-non-conjugated diene monomer is selected from diallyl oligomeric ethylene glycol, diallyl piperazine, diallyl ether, octadiene and the like, and the phosphorus source monomer is selected from diallyl oligomeric ethylene glycol, diallyl piperazine, diallyl ether, octadiene and the like. The phosphorus source monomer is selected from hypophosphorous acid and hypophosphite. The lithium salt compound polyelectrolyte based on the phosphorus-containing polymer has quite high conductivity and can be used for a lithium ion battery; the polyphosphonate surfactant disclosed by the invention has the characteristics of chemical stability, biocompatibility, hydrophilicity and the like, and the alkyl phosphonate surfactant shows diversified functions and purposes; the flame retardant based on the phosphorus-containing polymer has excellent flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional polymer materials, and specifically relates to a novel phosphorus-containing polymer, a preparation method of free radical addition polymerization under mild conditions and easy to implement, and its application, in particular to various functional polymer materials derived therefrom. Background Art

[0002] Since the 1940s, researchers have recognized the complexity and high value of phosphorus chemistry, and phosphorus chemistry research has achieved a large number of excellent research results in various aspects such as structure, bonding and reactivity, including many products with important industrial application value. In fact, phosphorus and carbon are in diagonal positions in the periodic table, and phosphorus is also called the carbon element model because many phosphorus-containing compounds show similar structures and behaviors to their corresponding carbon-based compounds (see K.Dillon, F.Mathey, JFNixon, In Phosphorus: The Carbon Copy, 1998). However, the research and development of phosphorus chemistry has been mostly limited to the small molecule level. It was not until recent years that significant progress was made in the research of phosphorus-containing polymers (see F. Mathey, Angew. Chem. Int. Ed. 2003, 42, 1578-1604; T. Baumgartner, R. Re′au, Chem. Rev. 2006, 106, 4681-4727; J. I. Bates, J. Dugal-Tessier, D. P. Gates, Dalton Trans. 2010, 39, 3151-3159). Phosphorus-containing polymer materials have many excellent properties such as flame retardancy, good metal adhesion, biodegradability and blood compatibility, so they are widely used in various fields such as textile finishing agents, flame retardants, adhesives and biopharmaceutical materials (see DASPiro, WCDarrell, RQDonna, Ind.Eng.Chem.Res., 1991, 30, 772-778; J.Canadell, BJAG Gunt Cook, Polym.Degrad.and Stabil., 2007, 92, 1482-1490; S. Monge, B. Canniccioni, A. Graillot, Biomacromolecules, 2011, 12, 1973-1982; KNBauer, HTTee, MMVe lencoso, FR Wurm, Prog. Polym. Sci., 2017, 73, 61-122; S. Hiranphinyophat, Y. Iwasaki, Sci. Technol. Adv. Mater., 2021, 22, 301-316).

[0003] Phosphorus of inorganic elements is introduced into organic high molecular polymers, which can be either main chain phosphorus-containing polymers or side chain phosphorus-containing polymers. Main chain phosphorus-containing polymer materials have some unique chemical functions, such as catalysts, sensors, biomaterials, etc. (see B. Thomas, R. Regis, Chem. Rev., 2006, 106, 4681-4727; K. Huynh, AJ Lough, I. Manners, J. Am. Chem. Soc., 2006, 128, 14002-14003). One major category of main chain phosphorus-containing polymers is polyphosphates (salts) based on main chain PO bonds, and another category is organic polyphosphine and its oxides or polyphosphonic acid (ester / salt) based on main chain PC bonds. Polyphosphate polymer materials have good biocompatibility, degradability and flame retardancy, but poor long-term hydrolysis resistance is also their biggest disadvantage in certain material applications. Therefore, their use is greatly limited in application scenarios where uncontrolled hydrolysis or excessively rapid hydrolysis is undesirable. Compared with polyphosphates, organic polyphosphonic acid (ester / salt) polymer materials overcome this obvious shortcoming. The PC bond therein is very resistant to oxidation and hydrolysis, and is even more stable than the CC bond in this respect. Therefore, the preparation and application of organic polyphosphonic acid (ester / salt) have attracted much attention (see S. Maiti, S. Banerjee, SK Palit, Prog. Polym. Sci., 1993, 18, 227-261; Y. Liu, N. Yan, F. Li, P. Chen, Polym. Int., 2013, 62, 390-396; KN Bauer, HTTee, I. Lieberwirth, FR Wurm, Macromolecules, 2016, 49, 3761-3768).

[0004] The research on polyphosphate polymer materials with PO bonds as the main chain has been quite in-depth. In recent years, there have been many new advances in the preparation of biomimetic phosphorus-containing polymers based on the functional modification of polyphosphate derivatives with PO bonds. For example, the prepolymer was converted into a non-cytotoxic and degradable thermoresponsive polymer that exhibited UCST behavior in the temperature range of 43 to 71°C in water by using two cyclic phosphate anions for ring-opening random copolymerization and then introducing side chain carboxylic acid modification through thiol-ene click reaction, so as to control the self-assembly and decomposition of block copolymers in water. Polyphosphate surfactants with different binding base sequences were synthesized by anionic ring-opening polymerization of cyclic phosphates. After the polyphosphate surfactants were wrapped around nanocarriers, the adsorption of blood proteins was reduced and the nanocarriers were prevented from being recognized by immune cells (macrophages). This strategy successfully transformed the nanocarriers into camouflaged nanocarriers with excellent biocompatibility by utilizing the chemical versatility of polyphosphates, which can be applied to advanced drug delivery systems (see J. Simon, T. Wolf, K. Klein, K. Landfester, FR Wurm, Angew. Chem. Int. Ed., 2018, 57, 5548-5553; KN Bauer, J. Simon, V. K. Landfester, FR Wurm, Acta Biomater., 2020, 116, 318-328).

[0005] The synthesis methods of organic polyphosphine or polyphosphonate (salt) based on PC bond, which have been reported so far, mainly include phosphine-ene polymerization, phosphorus-containing heterocyclic ring-opening polymerization, and polymerization of reactive multifunctional monomers with PC bond introduced by pre-synthesized PC bond (usually step-by-step polymerization such as polycondensation). Polyphosphine-ene is obtained by chain addition polymerization of phosphine-ene monomer (RP=CR'2). Such polymers have certain stability to air and water when in solid state, but after being dissolved in dichloromethane and exposed to air for four days, they are partially oxidized and become polyoxyphosphine-ene. Phosphorus-containing heterocyclic rings can also produce trivalent or pentavalent phosphorus main chain polymers through anion, cation or free radical reaction mechanisms. For example, Michelle explored the chain growth mechanism and kinetics of free radical-induced ring-opening polymerization of a series of phosphorus-containing heterocyclic rings through theoretical calculations, indicating that the most likely path is that carbon free radicals attack the phosphorus atom on the ring to initiate chain growth. However, no matter which active species mechanism of ring-opening polymerization is used, its phosphorus-containing cyclic monomer is not common and needs to be specially synthesized. The reaction conditions required for polymerization are also high, and it is not easy to achieve. In recent years, an indirect synthesis strategy has been formed by introducing PC bonds into multifunctional reactive monomers through relatively efficient reaction pathways such as click reactions to achieve the preparation of polymers containing PC bonds. Liu Chengmei et al. used tetrakishydroxymethylphosphonium sulfate (THPS) as a phosphorus source to synthesize a more stable and safe biscarbamate monomer with PC bonds, and further prepared polyurea with PC bonds through ester exchange. Recently, a styrene-derived multifunctional monomer with two epoxy groups introduced at the para position through a PC bond has been reported. The styrene and epoxy functional groups can be independently polymerized into chains without interfering with each other through free radical controlled polymerization or condensation polymerization to obtain a phosphorus-containing reactive polymer with a high density of functional groups (see CWTsang, M.Yam, DPGates, J.Am.Chem.Soc., 2003, 125, 1480-1481; LHJennifer, LCMichelle, Macromolecules, 2005, 38, 8902-8910; ZWTan, M.Zhang, HZGuo, JJQiu, CMLu, Des.Monomers Polym., 2014, 17, 762-774; J.Sun, YLHong, C.Wang, ZWTan, CMLu, Polym.Chem., 2022, 13, 1520-1536).

[0006] There are also some related patents for phosphorus-containing functional polymers, which are generally based on polyphosphates or polyphosphoramides. For example, Chinese patent CN 100445320 C uses lactic acid, diol compounds, and phosphorus-containing monomers to synthesize polyphosphates that can be used for sustained drug release through a melt process; Chinese patent CN 101914208 B uses diphosphoryl chloride or diphosphoryl bromide and diamine compounds through solution polycondensation or melt polycondensation to prepare polyphosphoramide-type intumescent flame-retardant polymers, which are used as additive flame retardants in flame-retardant formulations of various polymers such as polyester; Chinese patent application CN 114984236 A uses imidazole cationic monomers, phosphorylcholine-containing monomers and disulfide bond compounds through polymerization and cross-linking to prepare a surface-coated cross-linked polymer nucleic acid system, which has high stability and realizes a responsive nucleic acid delivery system.

[0007] It can be seen from the above patents and journal literature that there are very limited reports on phosphorus-containing polymers with PC bonds, and the existing systems either have cumbersome and time-consuming monomer preparation, or have harsh polymerization reaction conditions or obvious safety hazards. Summary of the invention

[0008] In view of this, the purpose of the present invention is to provide a phosphorus-containing polymer containing PC bonds and a preparation method and application thereof to address the technical problems existing in the prior art.

[0009] The objectives of the present invention are achieved through the following technical solutions.

[0010] The inventors of the present application have discovered that phosphorus-containing polymers are obtained by gradually polymerizing α,ω-non-conjugated diene functional monomers selected from bisallyl oligomer glycol, bisallyl piperazine, bisallyl ether and octadiene and cheap and readily available commercial raw materials such as hypophosphorous acid HPA or hypophosphite compounds through free radical addition under relatively mild reaction conditions. Such phosphorus-containing polymers can be used to further prepare phosphorus-containing functional polymer materials such as lithium salt complex polyelectrolytes, polyphosphonate surfactants and flame retardants, and have improved properties, thereby constituting the present invention.

[0011] In a first aspect, the present invention provides a phosphorus-containing polymer comprising PC bonds, wherein the phosphorus-containing polymer comprises repeating units derived from α,ω-non-conjugated diene monomers and repeating units derived from phosphorus source monomers, wherein the α,ω-non-conjugated diene monomers are selected from bisallyl oligomerized glycol, bisallyl piperazine, bisallyl ether and octadiene, and the phosphorus source monomers are selected from hypophosphorous acid and hypophosphite.

[0012] According to the phosphorus-containing polymer provided by the present invention, the number average molecular weight of the phosphorus-containing polymer is 1000-20000 g / mol, preferably 2000-15000 g / mol.

[0013] According to the phosphorus-containing polymer provided by the present invention, the molecular weight distribution index Mw / Mn of the phosphorus-containing polymer is 1.1-3.0, preferably 1.2-2.6.

[0014] According to the phosphorus-containing polymer provided by the present invention, wherein the degree of polymerization of the ethylene glycol unit in the bisallyl oligomerized ethylene glycol is 1-10 (in the present invention, the bisallyl oligomerized ethylene glycol reaction monomer can also be expressed as M(EG n ), wherein n=1-10). For example, the degree of polymerization of the ethylene glycol unit in the bisallyl oligomerized ethylene glycol may be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. The inventors have found that when the degree of polymerization of the bisallyl oligomerized ethylene glycol is above 8, the synthesis efficiency is reduced, and a small amount of crystallization peaks will appear, which will reduce the conductivity of the polyelectrolyte prepared therefrom. In some embodiments, the degree of polymerization of the ethylene glycol unit in the bisallyl oligomerized ethylene glycol is 2-7.

[0015] According to the phosphorus-containing polymer provided by the present invention, the phosphorus-containing polymer is a polymer obtained by stepwise polymerization of the α,ω-non-conjugated diene monomer and the phosphorus source monomer via free radical addition.

[0016] In a second aspect, the present invention provides a method for preparing a phosphorus-containing polymer comprising a PC bond, the preparation method comprising the following steps:

[0017] In the presence of a free radical initiator, an α,ω-non-conjugated diene monomer and a phosphorus source monomer are subjected to a free radical addition stepwise polymerization reaction, wherein the α,ω-non-conjugated diene monomer is selected from bisallyl oligomerized glycol, bisallyl piperazine, bisallyl ether and octadiene, and the phosphorus source monomer is selected from hypophosphorous acid and hypophosphite.

[0018] In the present invention, the α,ω-non-conjugated diene monomers such as bisallyl oligomerized ethylene glycol used are easy to synthesize or can be directly commercially obtained, and the phosphorus source monomers are cheap and easily available. Therefore, this easily achievable synthesis route (method) and its polymer product of the present invention have broad application prospects.

[0019] According to the preparation method provided by the present invention, the free radical addition stepwise polymerization reaction is carried out in the presence of a free radical initiator.

[0020] In the present invention, the free radical initiator can be an organic phase initiator and / or an aqueous phase initiator. The organic phase initiator can be an azo initiator or an organic peroxide initiator, for example, azobisisobutyronitrile (AIBN) or dibenzoyl peroxide (BPO), preferably azobisisobutyronitrile. The aqueous phase initiator can be a persulfate initiator or a water-soluble azo initiator, preferably a persulfate initiator, for example, sodium persulfate, potassium persulfate or ammonium persulfate.

[0021] In some embodiments, the free radical initiator is added in batches, for example, in 2-4 additions.

[0022] According to the preparation method provided by the present invention, the molar ratio of the α,ω-non-conjugated diene monomer, the phosphorus source monomer and the free radical initiator is 1:1:(0.05-0.75), preferably 1:1:(0.2-0.3), for example, 1:1:0.25; and / or the free radical initiator is selected from azobisisobutyronitrile, dibenzoyl peroxide and persulfate.

[0023] According to the preparation method provided by the present invention, the free radical addition stepwise polymerization reaction is carried out in the presence of a solvent. Examples of solvents suitable for use in the present invention include, but are not limited to, toluene, chlorobenzene, acetonitrile, tetrahydrofuran, 1,4-dioxane, n-propanol, isopropanol, n-butanol, methyl ethyl ketone, ethanol and dimethyl sulfoxide.

[0024] In some embodiments, the solvent is selected from chlorobenzene, n-propanol and ethanol, preferably ethanol. It is believed that the phosphorus-containing polymer prepared by using these solvents has a high degree of polymerization and a relatively low polydispersity index.

[0025] The present invention has no special requirements on the amount of solvent used. However, when the volume mass ratio of the solvent to the α,ω-non-conjugated diene monomer is 1.5-5.0 mL:1.0 g, preferably 2-3 mL:1.0 g, the reaction is better carried out.

[0026] According to the preparation method provided by the present invention, the conditions of the free radical addition step polymerization reaction include: temperature 50-100°C, preferably 75±5°C, reaction time 1-80h, preferably 36-72h; and / or, carried out in an inert atmosphere, preferably a nitrogen atmosphere; and / or, stirring speed 500-1500rpm, preferably 1000-1200rpm.

[0027] According to the preparation method provided by the present invention, the preparation method comprises the following steps:

[0028] S101, adding an α,ω-non-conjugated diene monomer, a phosphorus source monomer and a first portion of a free radical initiator to a solvent, mixing, introducing nitrogen gas to exclude oxygen, and obtaining a nitrogen atmosphere reaction system;

[0029] S102, carrying out a polymerization reaction at a temperature of 50 to 100° C., preferably 75±5° C., under stirring conditions for 1 to 80 hours, preferably 36 to 72 hours, to obtain a reaction product;

[0030] S103, adding ethanol to the reaction product for dilution to obtain a diluted reaction product, adding the diluted reaction product to petroleum ether for phase separation precipitation, removing the upper layer solvent, and drying to obtain a phosphorus-containing polymer.

[0031] Preferably, in step S102, a first portion of a free radical initiator is added to carry out a polymerization reaction, and during the polymerization reaction, in particular at intervals of 24-72 hours, a second portion of a free radical initiator and a third portion of a free radical initiator are added. Further preferably, the first portion of a free radical initiator, the second portion of a free radical initiator and the third portion of a free radical initiator each independently account for 30-40% of the total amount of the free radical initiator.

[0032] Preferably, in step S102, the stirring speed is 500-1500 rpm, preferably 1000-1200 rpm.

[0033] Preferably, in step S103, the drying temperature is 60-80°C.

[0034] In the present invention, in step S103, petroleum ether is added to perform phase separation and precipitation of the polymer, thereby removing the unreacted raw materials and low molecular weight polymers.

[0035] In a third aspect, the present invention provides a lithium salt complex polyelectrolyte, which comprises the phosphorus-containing polymer described in the first aspect or the phosphorus-containing polymer prepared by the preparation method described in the second aspect, and doped lithium trifluoromethanesulfonate.

[0036] In the present invention, compared with the lithium salt complex polyelectrolyte based on long-chain polyethylene glycol PEG, the lithium salt complex polyelectrolyte of the present invention has reduced AC impedance and improved ionic conductivity. It is believed that in the lithium salt complex polyelectrolyte of the present invention, the phosphorus-containing polymer of the short-chain oligoethylene glycol suppresses the crystallinity of the conventional long-chain polyethylene glycol PEG and improves the ionic conductivity of the obtained phosphorus-containing polymer polyelectrolyte.

[0037] According to the lithium salt complex polyelectrolyte provided by the present invention, the doping amount of the lithium trifluoromethanesulfonate salt is 0-50wt%, preferably 1-50wt%, and more preferably 5-30wt%, based on the mass of the lithium salt complex polyelectrolyte.

[0038] According to the lithium salt complex polyelectrolyte provided by the present invention, wherein the α,ω-non-conjugated diene monomer in the phosphorus-containing polymer is bisallyl oligomerized ethylene glycol. In the present invention, the bisallyl oligomerized ethylene glycol is as described in the first aspect. In some embodiments, the degree of polymerization of the ethylene glycol unit in the bisallyl oligomerized ethylene glycol is 2-7, for example, 2, 3, 4, 5, 6, 7.

[0039] In a fourth aspect, the present invention provides a method for preparing the lithium salt complex polyelectrolyte according to the third aspect, wherein the preparation method comprises:

[0040] S201, adding the phosphorus-containing polymer and LiCF3SO3 to the first reaction solvent, mixing, and obtaining a reaction system;

[0041] S202, reacting the reaction system in step S201 at a temperature of 60±5° C. and a rotation speed of 500-1200 rpm for 5-7 hours, and obtaining a lithium salt complex polyelectrolyte after drying.

[0042] According to the preparation method provided by the present invention, wherein, in step S201, the first reaction solvent is water, preferably ultrapure water.

[0043] According to the preparation method provided by the present invention, the mass ratio of the phosphorus-containing polymer to LiCF3SO3 in step S201 is 1:(0-1), preferably 1:(0.01-1), more preferably 1:(0.05-0.43), for example 17:3.

[0044] According to the preparation method provided by the present invention, the drying in step S201 includes: rotary evaporating the first reaction solvent to dryness; vacuum drying at a temperature of 60±5°C for 24 to 72 hours, preferably 36 to 48 hours; and keeping warm at a temperature of 100±5°C for 8 to 24 hours, preferably 12 to 18 hours.

[0045] In a fifth aspect, the present invention provides a polyphosphonate surfactant, which comprises the reaction product of the phosphorus-containing polymer described in the first aspect or the phosphorus-containing polymer prepared by the preparation method described in the second aspect, a catalyst and 1-bromododecane.

[0046] According to the polyphosphonate surfactant provided by the present invention, the catalyst is cesium carbonate.

[0047] According to the polyphosphonate surfactant provided by the present invention, the α,ω-non-conjugated diene monomer in the phosphorus-containing polymer is bisallyl oligomerized ethylene glycol. In some embodiments, the polymerization degree of the ethylene glycol unit in the bisallyl oligomerized ethylene glycol is preferably 2-7, for example 2, 5, 7.

[0048] According to the polyphosphonate surfactant provided by the present invention, the molar ratio of the phosphorus-containing polymer, the catalyst and 1-bromododecane is 1:(0.25-2):2, preferably 1:2:2, based on the total repeating units derived from α,ω-non-conjugated diene monomers and phosphorus source monomers in the phosphorus-containing polymer.

[0049] In the present invention, the term "based on the total repeating units derived from the α, ω-non-conjugated diene monomer and the phosphorus source monomer in the phosphorus-containing polymer" means that the amount of the substance of the phosphorus-containing polymer is calculated based on the molecular weight of the repeating units formed by the reaction of the α, ω-non-conjugated diene monomer and the phosphorus source monomer in the phosphorus-containing polymer, rather than calculating the amount of the substance based on the molecular weight of the phosphorus-containing polymer.

[0050] According to the polyphosphonate surfactant provided by the present invention, the polyphosphonate surfactant may be in the form of an aqueous solution.

[0051] In some embodiments, the concentration of the aqueous solution is 0.01-1 mg / mL, for example 0.1 mg / mL. At such a concentration, the polyphosphonate surfactant can assemble into a micellar structure that exhibits surfactant characteristics.

[0052] In a sixth aspect, the present invention provides a method for preparing the polyphosphonate surfactant described in the fifth aspect, wherein the preparation method comprises the following steps:

[0053] S301, adding the phosphorus-containing polymer, the catalyst, and 1-bromododecane to a second reaction solvent, introducing an inert gas to exclude oxygen, and obtaining a reaction system;

[0054] S302, at a temperature of 75±5° C. and under stirring conditions, subjecting the reaction system obtained in step S301 to an esterification reaction to obtain a reaction product;

[0055] S303, filtering the reaction product obtained in step S302 to remove the catalyst, adding ethanol to dilute the reaction product, adding petroleum ether for phase separation and precipitation, removing the upper liquid, and drying to obtain a polyphosphonate surfactant.

[0056] According to the preparation method provided by the present invention, wherein the second reaction solvent in step S301 is acetonitrile. An inert gas is introduced to exclude oxygen and then sealed. Examples of inert gases suitable for use in the present invention include, but are not limited to, argon and nitrogen.

[0057] According to the preparation method provided by the present invention, the time of the esterification reaction in step S302 is 12-36 hours.

[0058] According to the preparation method provided by the present invention, the stirring speed in step S302 is 500-1500 rpm, preferably 1000-1200 rpm.

[0059] According to the preparation method provided by the present invention, the drying in step S303 includes: rotary evaporating the precipitate obtained after removing the upper liquid to dryness; and vacuum drying at a temperature of 60±5°C.

[0060] In a seventh aspect, the present invention provides a flame retardant based on a phosphorus-containing polymer, wherein the flame retardant comprises the phosphorus-containing polymer described in the first aspect or a neutralization reaction product of the phosphorus-containing polymer prepared by the preparation method described in the second aspect and an alkaline substance.

[0061] According to the flame retardant provided by the present invention, the α,ω-non-conjugated diene monomer in the phosphorus-containing polymer is bisallylpiperazine.

[0062] According to the flame retardant provided by the present invention, the alkaline substance is selected from aluminum chloride and ammonia.

[0063] According to the flame retardant provided by the present invention, the molar ratio of the phosphorus-containing polymer to the alkaline substance is 1.8-2.2:1, based on the total repeating units derived from the α,ω-non-conjugated diene monomer and the phosphorus source monomer in the phosphorus-containing polymer.

[0064] In an eighth aspect, the present invention provides a method for preparing a flame retardant based on a phosphorus-containing polymer according to the seventh aspect, wherein the preparation method comprises:

[0065] The phosphorus-containing polymer, the alkaline substance and the third reaction solvent are mixed and stirred for reaction to obtain a flame retardant based on the phosphorus-containing polymer.

[0066] According to the preparation method provided by the present invention, the third reaction solvent is selected from water and ethanol.

[0067] According to the preparation method provided by the present invention, wherein the alkaline substance is aluminum chloride, the preparation method comprises:

[0068] S401, reacting a reaction system comprising a phosphorus-containing polymer, an alkaline substance and ethanol at a temperature of 70-85° C. and a rotation speed of 500-1200 rpm, preferably 1000-1200 rpm for 12-18 hours, and obtaining a flame retardant based on the phosphorus-containing polymer through washing and vacuum drying.

[0069] Preferably, in step S401, the molar ratio of the phosphorus-containing polymer to the alkaline substance is 1.8-2.2:1, for example 2:1.

[0070] Preferably, in step S401, the reaction system is formed by dropwise adding an ethanol solution of an alkaline substance into an ethanol solution of a phosphorus-containing polymer.

[0071] Preferably, in step S401, ethanol is used for washing.

[0072] Preferably, in step S401, the vacuum drying temperature is 60±5°C.

[0073] According to the preparation method provided by the present invention, wherein the alkaline substance is ammonia water, the preparation method comprises:

[0074] S402, reacting a reaction system comprising a phosphorus-containing polymer, an alkaline substance and water at a temperature of 20-30° C. and a rotation speed of 500-1200 rpm, preferably 1000-1200 rpm for 12-24 hours, and obtaining a flame retardant based on the phosphorus-containing polymer by vacuum drying.

[0075] Preferably, in step S402, the reaction system is prepared by the following method: adding ammonia water dropwise to an aqueous solution of the phosphorus-containing polymer until the pH is 10 to obtain the reaction system.

[0076] Preferably, in step S402, the vacuum drying temperature is 60±5°C.

[0077] According to the preparation method and application provided by the present invention, the stirring speed in steps S401 and S402 is 500-1200 rpm, preferably 1000-1200 rpm.

[0078] In a ninth aspect, the present invention provides a flame retardant epoxy resin, comprising a cured epoxy resin and the flame retardant of the seventh aspect or the flame retardant prepared by the preparation method of the eighth aspect dispersed therein.

[0079] According to the flame retardant epoxy resin provided by the present invention, the flame retardant epoxy resin comprises a reaction product of an epoxy resin, the flame retardant and a curing agent.

[0080] Examples of epoxy resins suitable for use in the present invention include, but are not limited to, E-51 and E-44. Examples of curing agents suitable for use in the present invention include, but are not limited to, 4,4′-diaminodiphenylmethane (DDM).

[0081] In some embodiments, the mass ratio of the epoxy resin, the flame retardant and the curing agent is 4:(0.05-0.55):(0.8-1.2), preferably 4:(0.05-0.55):1, and more preferably 4:0.26:1.

[0082] In a tenth aspect, the present invention provides a method for preparing the flame retardant epoxy resin of the ninth aspect, wherein the preparation method comprises:

[0083] S403, under stirring conditions, the epoxy resin, flame retardant and curing agent are mixed, and vacuum degassing and curing are performed.

[0084] According to the preparation method provided by the present invention, the specific steps of step S403 include: mixing and dispersing the epoxy resin and the flame retardant at a temperature of 115-125°C and a stirring speed of 800-1200rpm for 20-40min, cooling to 100-110°C, adding DDM and stirring, mixing and dispersing for 5-15min, and vacuum degassing at 115-125°C to obtain a prepolymer; transferring the prepolymer into a mold (preparing a test specimen), curing at 115-125°C for 1.5-2.5h, and then heating to 170±5°C for curing for 3-5h.

[0085] Compared with the prior art, the present invention has the following advantages:

[0086] (1) The present invention adopts the method of free radical stepwise addition polymerization for the first time, and realizes the free radical addition polymerization of readily available hypophosphorous acid or hypophosphite with α,ω-non-conjugated dienes compatible with a wide range of functional groups under mild reaction conditions, thereby preparing new organic phosphonic acid polymers (phosphorus-containing polymers) based on PC bonds and functional polymer materials derived therefrom, which provides a basis and a new path direction for the preparation of phosphorus-containing polymer materials based on PC bonds and has broad application prospects.

[0087] (2) In existing battery electrolytes and related research reports, conventional battery electrolytes are prone to crystallization at low temperatures, resulting in low conductivity, dendrite puncture, leakage and damage. For example, the most commonly used polyelectrolytes based on polyethylene glycol (PEG) are prone to crystallization at room temperature, inhibiting the movement of chain segments and significantly reducing the conductivity of PEG / lithium salt polymer electrolytes. The lithium salt complex polyelectrolyte based on oligoethylene glycol phosphorus-containing polymer prepared by the present invention is amorphous at room temperature, completely avoiding the usual crystallization inhibition of PEG, and significantly improving the Li + The mobility and conductivity of the material can be used in lithium-ion batteries.

[0088] (3) High molecular surfactants have good emulsification, coagulation, dispersion, washing and low toxicity. At present, a variety of polyphosphate surfactants have been reported, but in order to meet the special use requirements of this type of phosphate surfactant, polyphosphates with higher purity requirements need to be prepared by other methods, such as using phosphorus oxychloride to prepare monoesters; using phosphorus trichloride to prepare diesters, the toxicity and danger of the raw materials required are greatly increased. Based on the prepared phosphorus-containing polymer, the present invention obtains a polyphosphonic acid long-chain alkyl ester surfactant after partial esterification modification. At the same time, combined with the excellent chemical stability and biocompatibility of the PC bond polymer and the good hydrophilicity of the remaining part of the polyphosphonic acid anions, it can be assembled into micelles in the solution and has the diversified functional uses of organic polyphosphonic acid alkyl ester surfactants.

[0089] (4) Another major advantage of phosphorus-containing polymers is their excellent flame retardant properties. Due to environmental protection requirements, the use of halogen flame retardants is strictly restricted, and halogen-free flame retardants such as phosphorus-based and phosphorus-nitrogen synergistic flame retardants are becoming more and more popular. However, small molecule flame retardants have the disadvantage of being prone to phase separation in polymer materials due to poor compatibility, while polymer macromolecular flame retardants have the advantage of greater compatibility. The phosphorus-containing polymer polyP (Pz) of the present invention is further used to prepare aluminum salt or ammonium salt flame retardants of the polymer, which synergistically improve the flame retardancy of flame-retardant polymer materials.

[0090] (5) In the preparation method of the phosphorus-containing polymer of the present invention, the polymerization reaction operation is carried out under conventional mild conditions, without the need for special operations or facilities (such as glove boxes, etc.), the solvents and other chemical reagents used are used directly, and the raw materials are not highly toxic or highly corrosive and difficult to handle. Hypophosphorous acid or sodium hypophosphite is economical and easy to obtain, the synthesis of α, ω-non-conjugated diene monomers is simple and efficient, and the polymerization reaction yield is high. This type of addition-type step-by-step polymerization does not remove small molecules, is more in line with atom economy, and is conducive to the large-scale expansion and application of this type of new free radical addition-type step-by-step polymerization. BRIEF DESCRIPTION OF THE DRAWINGS

[0091] The drawings constituting part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention.

[0092] Figure 1 It is the nuclear magnetic hydrogen spectrum and phosphorus spectrum NMR spectrum of the phosphorus-containing polymer polyP (EG5) of the present invention.

[0093] Figure 2 The phosphorus-containing polymer polyP(EG n )(n=2~7) and the comparison graph of the ionic conductivity of PEG doped with 15wt% LiCF3SO3 as a function of temperature.

[0094] Figure 3 The phosphorus-containing polymer polyP(EG n )(n=2~7) and comparative PEG doped with 15wt% LiCF3SO3 respectively.

[0095] Figure 4 These are the TEM test analysis and dynamic light scattering (DLS) characterization results of micelles assembled from dodecyl ester surfactants of oligomeric polyethylene glycol polyphosphonic acid of different lengths in 0.1 mg / mL aqueous solution: (a) polyP(EG2)-C12; (b) polyP(EG5)-C12; (c) polyP(EG7)-C12; (d) DLS graph.

[0096] Figure 5 These are actual photos of blank control and composite flame retardant epoxy resin sample strips: (a) blank sample strip; (b) composite flame retardant epoxy resin sample strip with 1% polyP(Pz)Al added; (c) composite flame retardant epoxy resin sample strip with 1% polyP(Pz)NH4 added; (d) composite flame retardant epoxy resin sample strip with 5% polyP(Pz)Al added; (e) composite flame retardant epoxy resin sample strip with 5% polyP(Pz)NH4 added.

[0097] Figure 6 These are the TGA graphs of four groups of composite flame-retardant epoxy resins and blank control samples in (a) nitrogen atmosphere and (b) air atmosphere. DETAILED DESCRIPTION

[0098] The present invention is further described below in conjunction with the accompanying drawings and embodiments. The following description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0099] Chemical reagents: hypophosphorous acid (50 wt% aqueous solution, McLean); 2,2-azobisisobutyronitrile (98%, Aladdin); anhydrous potassium carbonate (AR, Sinopharm-Shanghai test); propylene bromide (98%, Myrel); ammonia (AR25.0-28.0%, Sinopharm-Shanghai test); diethylene glycol (CR, Sinopharm-Shanghai test); triethylene glycol (AR, Sinopharm-Shanghai test); tetraethylene glycol (99%, Aladdin); pentaethylene glycol (97%, Myrel); hexaethylene glycol (97%, Aladdin); heptaethylene glycol (95%, Acce la); (diethylene glycol to heptaethylene glycol are all oligoethylene glycols); lithium trifluoromethanesulfonate (98%, MacLean); polyethylene glycol (number average molecular weight is 6000g / mol, MacLean); piperazine (99%, Sinopharm-Shanghai test); allyl chloride (CP, Sinopharm-Shanghai test); aluminum chloride hexahydrate (AR, Nan test); epoxy resin (E-51, MacLean); 4,4′-diaminodiphenylmethane (AR, Sinopharm-Shanghai test); high vacuum silicone grease (7051, ReLAB); anhydrous sodium sulfate (AR, Sinopharm-Shanghai test); hydroxide Sodium (AR, Sinopharm-Shanghai test); high-purity nitrogen (≥99.5%, Nanjing Shangyuan Gas Plant); 1-bromodecane (98%, J&K); pyrene (97%, Bidex Pharmaceuticals); butane gas (≥95%, Iwatani); dimethyl sulfoxide (AR, Sinopharm-Shanghai test); N,N-dimethylformamide (AR, Sinopharm-Shanghai test); methanol (AR, Yashi); ethanol (AR, Yashi); n-propanol (AR, Sinopharm-Shanghai test); isopropanol (AR, Sinopharm-Shanghai test); n-butanol (AR, Nanshi); methyl ethyl ketone (AR, Nanshi); chlorobenzene (AR, Shanghai Lingfeng); toluene (AR, Nanshi); acetonitrile (AR, Shanghai Lingfeng); tetrahydrofuran (AR, Maclean); 1,4-dioxane (AR, Sinopharm-Shanghai Trial); chloroform (AR, Nanshi); ethyl acetate (AR, Yashi); dichloromethane (AR, Yashi); petroleum ether (AR, Yashi); acetone (AR, Shanghai Lingfeng); 1,4-dioxane (AR, Sinopharm-Shanghai Trial); deuterated chloroform (0.03% TMS, 99.8% D, Bailingwei).

[0100] In addition, reagents not listed are all conventional reagents in the art and can be prepared or purchased.

[0101] Silica gel with a mesh size of 200 to 300 was used in the chromatography column, and the color was observed by an iodine cylinder.

[0102] Nuclear magnetic resonance spectroscopy ( 1 H NMR and 31 P NMR)

[0103] A German Bruker Avance III 400MHz liquid nuclear magnetic resonance spectrometer was used, and CDCl3 was used as the deuterated reagent. 1 H NMR uses tetramethylsilane TMS as an internal standard and the corresponding residual solvent hydrogen proton peak CDCl3 (δ=7.26) in the deuterated solvent as an auxiliary reference. 13 C NMR referenced to CDCl3 (δ=77.16).

[0104] Fourier Transform Infrared Spectroscopy (FT-IR)

[0105] Thermo Scientific Nicolet iS10 FTIR spectrometer was used in the United States. The attenuated total reflection mode was used for direct testing, or the potassium bromide tablet method was used for transmission testing. The test scanning range was 4000-400cm -1 .

[0106] Aqueous Gel Permeation Chromatography (Aqueous GPC)

[0107] A British Agilent Technologies PL-GPC50 aqueous gel permeation chromatograph was used, equipped with a differential refractometer. The mobile phase was 0.1 M sodium nitrate aqueous solution. The temperature was constant at 35°C, the flow rate was set to 1.0 mL / min, and the test sample was configured as a 2 mg / mL sodium nitrate aqueous solution. It was filtered using a polyethersulfone filter membrane with a pore size of 0.45 μm. The test results were calibrated and calculated for relative molecular mass using polyethylene glycol (PEG) standards.

[0108] High Resolution Mass Spectrometry (HRMS)

[0109] The German Thermo Fisher Q Exactive electrospray quadrupole-orbitrap tandem high-resolution mass spectrometer was used for testing in electrospray ionization (ESI) mode or atmospheric pressure chemical ionization (APCI) mode. The test range was 100.0000–1500.0000 g / mol, and the samples were prepared into 1 μg / mL methanol or dichloromethane solution for testing.

[0110] Fluorescence emission spectroscopy analysis

[0111] A Japanese Shimadzu RF-5301PC fluorescence spectrophotometer was used, the light source was a 150W xenon lamp, and the wavelength measurement range was 220-900nm.

[0112] Thermogravimetric analysis (TGA)

[0113] A Swiss Mettler Toledo TGA 1 / 1100LF synchronous thermogravimetric analyzer was used. During the test, 5-20 mg of accurately weighed sample was placed in a 70 μL alumina crucible with nitrogen or air purging at 20 mL / min. A crucible of the same standard was used as a reference, and the temperature was gradually increased from room temperature to 800°C at a heating rate of 20°C / min.

[0114] X-ray powder diffraction analysis (XRD)

[0115] The German Panalytical XPERT Powder X-ray powder diffractometer was used for the test. The specific method was as follows: about 0.1g of powder sample was placed on a glass slide, compacted and tested, with Cu-Kα as the radiation source and a wavelength of The scanning range is 2θ=5°-90°.

[0116] Dynamic Ionic Conductivity (DIC)

[0117] A Princeton VersaSTAT 3F electrochemical workstation from the United States was used, equipped with a Leitz-350 temperature-controlled hot stage and VersaStudio processing software. The test was performed in AC impedance mode with an amplitude voltage of 0.3 V, a start frequency of 100 Hz, and an end frequency of 1 MHz. The impedance spectrum was tested every 10°C rise from room temperature.

[0118] Dynamic Laser Light Scattering (DLS)

[0119] The US Brookhaven BI-200SM dynamic laser light scattering instrument was used, with a 532nm green light source, a test angle of 90°, and a test temperature of 25°C. The CONTIN mode was used to analyze the correlation function of the data to obtain the hydrodynamic average diameter D of the assembled particles. h And the particle size polydispersity index PSD.

[0120] Transmission electron microscopy analysis (TEM)

[0121] Using a Japanese JEOL JEM-2100 transmission electron microscope, 7 μL of the sample solution to be tested was dropped onto a 200-mesh carbon support film TEM copper grid produced by Zhongjing Keyi, and the morphology was observed and photographed after it was completely evaporated.

[0122] Limiting Oxygen Index Test (LOI)

[0123] The oxygen index tester of Nanjing Leijiong Instruments, China, was used. It was equipped with a heat-resistant glass tube with an inner diameter of 80 mm, a height of 450 mm, an inner diameter of 40 mm at the top outlet, and a butane gas igniter. The top ignition method was used for testing. The test method was based on GB / T2406-93. The oxygen index expressed in volume percentage was calculated according to formula (1):

[0124]

[0125] In formula (1), LOI is the limiting oxygen index, %;

[0126] ——The last oxygen concentration of the NT series measured, with one decimal place, %;

[0127] d——the difference between the two oxygen concentrations during the test, i.e. the step length, with one decimal place;

[0128] K——The corresponding coefficient provided by GB / T 2406-93.

[0129] Preparation Example 1: Synthesis of bis(allyl diglycol) ether M (EG2)

[0130] In a 100 mL flask, weigh diethylene glycol (3.18 g, 30 mmol), propylene bromide (12.70 g, 105 mmol), flaky solid sodium hydroxide catalyst (3.00 g, 75.0 mmol), and 40 mL of toluene solvent. Heat to 45 °C and stir to react for 24 h.

[0131] After the reaction is completed, the catalyst sodium hydroxide is removed by suction filtration, and the solvent is evaporated to dryness to remove all the solvent. 150 mL of dichloromethane is added, and after washing with 3×100 mL of water, the organic phases are combined, anhydrous sodium sulfate is added to dry and remove water, the solvent is evaporated to dryness and separated by a chromatography column (the eluent is ethyl acetate), and 3.92 g of light yellow liquid is obtained after vacuum drying, which is the monomer M (EG2) of bisallyl diglycol ether, and the yield is 70.2%.

[0132] Diallyl diglycol ether monomer M(EG2) 1 H NMR (400MHz, CDCl3, 298K, δin ppm): 5.97-5.87(m,2H), 5.30-5.16(m,4H), 4.04-4.02(m,4H), 3.69-3.60(m,8H). 13 C NMR (100MHz, CDCl3, 298K, δin ppm): 134.86, 117.12, 72.30, 70.75, 69.52. HRMS (ESI) (m / z): [M+Na] + calc.for C10 H 18 NaO3 + ,209.1154;found,209.1143.

[0133] Preparation Example 2-6: Synthesis of bisallyl tri-, tetra-, penta-, hexa-, and heptaglycol ether monomers

[0134] Diallyl triethylene glycol ether monomer M (EG3), bisallyl tetraethylene glycol ether monomer M (EG4), bisallyl pentaethylene glycol ether monomer M (EG5), bisallyl hexaethylene glycol ether monomer M (EG6) and bisallyl heptaethylene glycol ether monomer M (EG7) were synthesized by a method substantially the same as that in Preparation Example 1, except that equal amounts of triethylene glycol, tetraethylene glycol, pentaethylene glycol, hexaethylene glycol and heptaethylene glycol were used to replace diethylene glycol in Preparation Example 1, respectively, and the properties, yield and 1 H NMR, 13 C NMR and HRMS are as follows.

[0135] Diallyl triethylene glycol ether monomer M (EG3): light yellow liquid, yield 75.4%; 1 H NMR (400MHz, CDCl3, 298K, δin ppm): 5.96-5.87(m,2H),5.30-5.16(m,4H),4.04-4.01(m,4H),3.67-3.65(m,8H),3.65-3.59(m,4H). 13 C NMR (100MHz, CDCl3, 298K, δin ppm): 134.85, 117.16, 72.31, 70.72, 69.51. HRMS (ESI) (m / z): [M+Na] + calc.for C 12 H 22 NaO4 + ,253.1416;found,253.1403.

[0136] Diallyl tetraglycol ether monomer M (EG4): light yellow liquid; yield 79.5%; 1 H NMR (400MHz, CDCl3, 298K, δin ppm): 5.96-5.87(m,2H),5.29-5.16(m,4H),4.03-4.02(d,4H),3.66(d,12H),3.61-3.59(m,4H). 13C NMR (100MHz, CDCl3, 298K, δin ppm): 134.84, 117.16, 72.30, 70.70, 69.50. HRMS (ESI) (m / z): [M+Na] + calc.for C 14 H 26 NaO5 + ,297.1678;found,297.1662.

[0137] Diallyl pentaethylene glycol ether monomer M (EG5): light yellow liquid; yield 75.9%; 1 H NMR (400MHz, CDCl3, 298K, δin ppm): 5.96-5.87(m,2H),5.29-5.17(m,4H),4.03-4.02(d,4H),3.66(m,16H),3.66-3.59(m,4H). 13 C NMR (100MHz, CDCl3, 298K, δin ppm): 134.85, 117.13, 72.30, 70.67, 69.50. HRMS (ESI) (m / z): [M+Na] + calc.for C 16 H 30 NaO6 + ,341.1940;found,341.1925.

[0138] Diallyl hexaglycol ether monomer M (EG6): light yellow liquid; yield 73.2%; 1 H NMR (400MHz, CDCl3, 298K, δin ppm): 5.96-5.87(m,2H),5.30-5.17(m,4H),4.04-4.02(d,4H),3.67(m,20H),3.65-3.59(m,4H). 13 C NMR (100MHz, CDCl3, 298K, δin ppm): 134.83, 117.12, 72.28, 70.65, 69.49. HRMS (ESI) (m / z): [M+Na] + calc.for C 18 H 34 NaO7 + ,385.2202;found,385.2186.

[0139] Diallyl heptaglycol ether monomer M (EG7): light yellow liquid; yield 70.9%; 1H NMR (400MHz, CDCl3, 298K, δin ppm): 5.96-5.85(m,2H),5.29-5.15(m,4H),4.03-4.00(d,4H),3.66(m,24H),3.64-3.58(m,4H). 13 C NMR (100MHz, CDCl3, 298K, δin ppm): 134.82, 117.17, 72.29, 70.63, 69.49. HRMS (ESI) (m / z): [M+Na] + calc.for C 20 H 38 NaO8 + ,429.2464;found,429.2439.

[0140] Preparation Example 7: Synthesis of Diallylpiperazine Monomer M(Pz)

[0141] In a 100mL flask, weigh 14mL of a saturated aqueous solution of anhydrous piperazine (4.30g, 0.050mol) and anhydrous potassium carbonate (15.00g, 0.108mol), place in an ice-water bath, slowly add allyl chloride (8.42g, 0.110mol) through a constant pressure dropping funnel for 1h, and stir the reaction at room temperature for 24h after the addition is complete.

[0142] After the reaction, the mixture was extracted with 3×50 mL of dichloromethane, the organic phases were combined, and anhydrous sodium sulfate was added to dry the mixture. The solution was evaporated to dryness and then separated by a chromatography column (dichloromethane: methanol v / v = 10:1). After vacuum drying, 6.70 g of a yellow liquid was obtained, which was the bisallylpiperazine monomer M (Pz), with a yield of 80.6%.

[0143] Bis-allylpiperazine monomer M(Pz) 1 H NMR (400MHz, CDCl3, 298K, δin ppm): 5.88-5.78(m,2H),5.18-5.09(m,4H),2.98-2.96(m,4H),2.47(s,8H). 13 C NMR (100MHz, CDCl3, 298K, δinppm): 134.97, 118.07, 61.39, 53.01. HRMS (ESI) (m / z): [M+H] + calc.for C 10 H 19 N2 + ,167.1548;found,167.1539.

[0144] Example 1

[0145] This example is used to illustrate the effect of solvent on the step-wise addition polymerization of hypophosphorous acid and bisallyl pentaethylene glycol ether.

[0146] According to the initial feed molar ratio of [M(EG5)]0:[HPA]0:[AIBN]0=1:1:0.25, bis(allyl pentaglycol ether) M(EG5) (318 mg, 1 mmol), hypophosphorous acid HPA (66 mg, 1 mmol), and initiator AIBN (14 mg, 0.083 mmol) were added to different solvents (0.75 mL) as shown in Table 1, a stirring bar was added, and after three deoxygenation and inert gas (nitrogen) operations, the U-shaped tube was sealed with silicone oil. The Shrek bottle was then transferred to a magnetic stirrer set at a speed of 1000 rpm and subjected to polymerization reaction under oil bath heating (75°C) conditions (14 mg of AIBN was added every 24 hours, for a total of three times). After a total reaction time of 72 hours, the sealed container was taken out and opened, the polymerization system was diluted with ethanol (1 mL), poured into about 40 mL of petroleum ether, and separated by phase separation "precipitation" in a round-bottom flask, the upper layer of solvent was removed by decantation, the remaining small amount of solvent was removed by rotary evaporation, and the polymer product was obtained by drying under vacuum at 60°C.

[0147] Table 1. Effect of solvent on the polymerization of hypophosphorous acid and bis(allyl pentaethylene glycol ether)

[0148]

[0149] Remark: a Obtained by gravimetric analysis; b Obtained by aqueous GPC test calibrated with polyethylene glycol standards; c Obtained through GPC testing; d Can't get.

[0150] As shown in Experiment 1-1, under the conditions of solvent-free bulk melt reaction, hypophosphorous acid and bisallyl pentaglycol ether undergo violent polymerization, resulting in cross-linking, and the resulting block product has only a certain swelling property but cannot be dissolved. As shown in Experiments 1-2 to 1-12, polymerization reactions were carried out in different solvents (toluene, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, 1,4-dioxane, n-propanol, isopropanol, n-butanol, methyl ethyl ketone, chlorobenzene, ethanol), and the number average molecular weight of the obtained polymerization product was in the range of 5000-10000 g / mol, and the molecular weight polydispersity index was 1.65-2.57, which is a reasonable range for step-by-step polymerization. When chlorobenzene, n-propanol and ethanol were used as polymerization solvents, the polymerization degree based on GPC test exceeded 20. When ethanol was used as the polymerization solvent, the number average molecular weight of the polymerization product reached 9500 g / mol, the polymerization degree was 24, and the polydispersity index was 1.82. Therefore, ethanol is a relatively ideal solvent. In the following experiments, ethanol was mainly used as the polymerization solvent.

[0151] Example 2

[0152] This example is used to illustrate the effect of polymerization time on the step-wise addition polymerization of hypophosphorous acid and bisallyl pentaethylene glycol ether.

[0153] According to the initial molar ratio of [M(EG5)]0:[HPA]0:[AIBN]0=1:1:0.25, add bis(allyl) pentaethylene glycol ether M(EG5) (636mg, 2mmol), hypophosphorous acid HPA (132mg, 2mmol), initiator AIBN (27mg, 0.17mmol) into the ethanol solvent system (1.5mL), put in a stirrer, deoxygenate and pass inert gas (argon or nitrogen) three times, and seal the U-shaped tube with silicone oil. Then transfer the Shrek bottle to a magnetic stirrer set at 1000rpm and heat in an oil bath (75℃) for polymerization. After reaching the specified polymerization time (if it exceeds 24h, add 27mg of AIBN every 24h, for a total of three times). After the reaction is completed, the temperature is cooled to room temperature, and the sealed container is taken out and opened. The polymerization system is diluted with ethanol (1 mL), poured into about 35 mL of petroleum ether, and separated by phase "precipitation" in a round-bottom flask. The upper layer of solvent is removed by decantation, and the remaining small amount of solvent is removed by rotary evaporation. The polymer product is thoroughly dried under vacuum at 60°C to obtain.

[0154] Table 2. Effect of polymerization time on the polymerization of hypophosphorous acid and bis(allyl pentaethylene glycol ether)

[0155]

[0156] Remark: a Obtained by gravimetric analysis; b Obtained by aqueous GPC test calibrated with polyethylene glycol standards; c Obtained through GPC testing; d Can't get.

[0157] The time analysis of the step-by-step polymerization reaction can determine the degree of polymerization reaction. As shown in Table 2, the entire polymerization process can be divided into three stages, corresponding to the three batches of initiator AIBN addition. In the first stage, HPA and M(EG)5 are quickly converted into lower molecular weight oligomers with a number average molecular weight of 2000-3000 g / mol, and the yield at this time is less than 50%; in the last two stages of polymerization, the conversion rate continues to increase, but it is quite slow, reaching 63.4% and 80.1% in the second and third stages, respectively. The substantial reduction in the polymerization rate in the last two stages is mainly due to the significant decrease in the concentration of HPA and M(EG)5 monomers in the system. With the continuous addition of AIBN to further supplement free radicals, the oligomers are gradually converted into higher molecular weight polymers until the maximum yield is about 80%. The GPC characterization results further confirmed that after the batch addition of AIBN, the molecular weight of the polymer product of the step-by-step polymerization continued to increase in the three stages of the entire polymerization process, and the PDI was about 1.5-1.8.

[0158] According to Experiment 2-12, a phosphorus-containing polymer polyP (EG5) was prepared. The results of its hydrogen and phosphorus NMR characterization analysis are as follows: Figure 1 shown. Figure 1 middle 1 H proton peak and 31 The clear attribution of the P phosphorus peak confirms the structural correctness of polyP(EG5), indicating that under the optimized polymerization reaction conditions, the preparation of the new phosphorus-containing polymer polyP(EG5) with the target composition structure was successfully and efficiently achieved. This laid a foundation for the systematic development of the preparation of lithium salt polyelectrolytes and the subsequent further modification of polymers after esterification to achieve functionally adjustable phosphorus-containing surfactant materials and the expansion of functional polymers.

[0159] Example 3

[0160] This example is used to illustrate the phosphorus-containing polymer polyP (EG n Preparation and characterization of )(n=2~7).

[0161] The phosphorus-containing polymer was prepared according to the method of Experiment 2-12, except that the α,ω-non-conjugated diene monomer was changed to M(EG n )(n=2~7), a series of phosphorus-containing polymers polyP(EG n )(n=2-7). Table 3 shows the characterization results of the stepwise addition polymerization of bisallyl n-glycol ether (oligoethylene glycol) monomer and hypophosphorous acid.

[0162] Table 3. Addition polymerization of bisallyl n-glycol ether monomer and hypophosphorous acid and characterization results

[0163]

[0164] Remark: a Obtained by gravimetric analysis; b Obtained by aqueous GPC test calibrated with PEG standards; c Obtained through GPC testing.

[0165] As can be seen from Table 3, under the above optimized reaction conditions, the yield of the poly(ethylene glycol) polyphosphonic acid polymer prepared by the polymerization of the functional non-conjugated diene monomer and hypophosphorous acid is relatively high (>70%), the degree of polymerization is around 20 (19-24), which is relatively consistent, and the molecular weight distribution also conforms to the stepwise polymerization characteristic range (1.24-2.32), which provides a basis for the preparation of functional polyelectrolyte composite materials.

[0166] Example 4

[0167] This example is used to illustrate the preparation and characterization of phosphorus-containing polymer lithium salt complex polyelectrolyte materials.

[0168] 1. Preparation of phosphorus-containing polymer lithium salt complex polyelectrolyte materials

[0169] According to the scaled-up experiment of Experiment 3-1, polyP (EG2) was prepared by weighing 0.1 g of polyP (EG2) sample and 0.015 g of lithium trifluoromethanesulfonate (accounting for 15 wt% of the polymer sample), dissolving them in 10 mL of ultrapure water, and then transferring the flask to a magnetic stirrer set at a speed of 1000 rpm and heating it in an oil bath (60°C) for doping reaction preparation. After 6 hours, the water was evaporated to dryness, vacuum dried at 60°C for 48 hours, and kept at 100°C for 12 hours.

[0170] Based on experiments 3-2 to 3-6, several other polymers of the same series, polyP(EG3), polyP(EG4), polyP(EG5), polyP(EG6), polyP(EG7) and comparative polyethylene glycol PEG(M n =6000g / mol) and 15wt% of lithium trifluoromethanesulfonate salt.

[0171] 2. Ionic conductivity and powder diffraction XRD characterization analysis of composite polyelectrolyte

[0172] The composite polyelectrolyte was subjected to AC impedance test and powder X-ray diffraction (XRD) characterization analysis. The ionic conductivity of the composite polyelectrolyte was tested by electrochemical impedance spectroscopy (EIS) at a test frequency of 10 6 ~10Hz, amplitude 800mV, the test instrument is Princeton multi-channel electrochemical workstation. The test is carried out using the interdigital electrode method, and the test temperature range is 30~140℃. Figure 2 The prepared phosphorus-containing polymer polyP(EG nThe ionic conductivity curves of the composite polyelectrolytes of PEG (n=2-7) and control example PEG doped with 15 wt% LiCF3SO3 as a function of temperature are shown in Table 4. n The range of changes in AC impedance and ionic conductivity of the composite polyelectrolyte doped with 15wt% LiCF3SO3 at different temperatures (n=2-7) and the control example PEG. Figure 2 As can be seen from Table 4, with the increase of the length of the polyethylene glycol chain in the polymer, the ionic conductivity at 30 °C increases from 1.13×10 -6 Significantly increased to 1.58×10 -4 S / cm, and compared with the control PEG-based polyelectrolyte, the oligoethylene glycol P(EG n ) The ionic conductivity of polyelectrolytes with n above 4 is significantly improved. As the temperature increases, the ionic conductivity increases and can be increased to 10 -3 The order of magnitude is S / cm.

[0173] Table 4. Range of AC impedance and ionic conductivity of composite polyelectrolytes at different temperatures

[0174]

[0175] Figure 3 The prepared phosphorus-containing polymer polyP(EG n XRD spectra of composite polyelectrolytes of PEG-15wt%LiCF3SO3 (n=2-7) and control example PEG-15wt%Li + It can be seen that there are obvious PEG crystallization characteristic diffraction peaks at 2θ=19° and 25°, while the composite polyelectrolyte samples prepared by the present invention do not show obvious crystallization peaks, and only have broad peaks between 2θ=10° and 30°, indicating its amorphous polymer characteristics. The phosphorus-containing polymer lithium salt composite polyelectrolyte based on poly(ethylene glycol) completely inhibits the crystallization of PEG within the range of the investigated polymers. It is believed that the ion conduction of the lithium salt polyelectrolyte based on PEG occurs in the amorphous region, so the ion conductivity of such materials is significantly enhanced by inhibiting PEG crystallization, which is more conducive to ion conduction. Combining diffraction analysis and ion conductivity testing, it can be seen that the phosphorus-containing ion polymer based on PC bonding provides a new idea for the design and preparation of high-performance battery polyelectrolyte materials.

[0176] Example 5

[0177] This example is used to illustrate the preparation and characterization of a dodecyl ester surfactant of a phosphorus-containing polymer.

[0178] 1. Preparation of dodecyl ester surfactants of poly(ethylene glycol) phosphorus-containing polymers of different lengths

[0179] According to the proportional scale-up experiment of Experiment 3-1, polyP(EG2) was prepared. PolyP(EG2) (0.480 g, 2 mmol, based on the molecular weight of the repeating unit), 1-bromododecane (0.997 g, 4 mmol), catalyst cesium carbonate (1.303 g, 4 mmol), and 3 mL of acetonitrile solvent were weighed into an ampoule, and a stirrer was placed. After three deoxygenation and inert gas (argon or nitrogen) operations, the ampoule was sealed. Then the ampoule was transferred to a magnetic stirrer set at 1000 rpm and heated in an oil bath (75°C) for reaction. After 24 hours, cesium carbonate was removed by suction filtration, 5 mL of ethanol was added to dilute the reaction solution, and about 80 mL of petroleum ether was added dropwise to separate the phases in a round-bottom flask by "precipitation". The upper layer of solvent was removed by decantation, and the remaining small amount of solvent was completely removed by rotary evaporation. The ampoule was thoroughly dried under vacuum at 60°C to obtain 0.694 g of a light yellow viscous liquid, namely polyP(EG2)-C12.

[0180] Based on experiments 3-4 and 3-6, the dodecyl ester surfactants of the other two polymers of the same series, polyP(EG5) and polyP(EG7), polyP(EG5)-C12 and polyP(EG7)-C12, were prepared in the same manner. The esterification degrees of dodecyl esters of oligomeric ethylene glycol phosphorus-containing polymers of different lengths are shown in Table 5.

[0181] Table 5. Degree of esterification of dodecyl esters of oligomeric ethylene glycol phosphorus-containing polymers of different lengths

[0182]

[0183] Remark: a The degree of esterification was calculated from the area ratio of the characteristic peaks in H-NMR spectrum.

[0184] 2. Solution assembly behavior of phosphorus-containing polymer dodecyl ester surfactants and their polymer nanomicelles preparation

[0185] Weigh 10 mg of the dodecyl ester surfactant sample of the phosphorus-containing polymer, dissolve it in 2 mL of THF, add a stirrer, and stir at room temperature for 1 hour to fully dissolve it. Add 10 mL of ultrapure water dropwise to the above solution, stir at room temperature for 0.5 hours, and then remove THF by rotary evaporation at 20°C for 2 hours. Finally, add 90 mL of ultrapure water to obtain a 0.1 mg / mL polymer assembly solution. Then use a pipette to take the sample solution (7 μL) and drop it onto a carbon-coated copper grid. After drying at room temperature for 24 hours, perform TEM test characterization, and the remaining same solution is subjected to DLS test. The results are shown in Figure 4 and Table 6.

[0186] Table 6. Particle size of micellar particles assembled from dodecyl esters of phosphorus-containing polymers in 0.1 mg / mL aqueous solution

[0187]

[0188]

[0189] Figure 4 a-4c show the TEM images of polyP(EG2)-C12, polyP(EG5)-C12, and polyP(EG7)-C12, respectively. It can be seen from the figure that when the concentration of the assembly solution is 0.1 mg / mL, the three groups of phosphorus-containing polymer dodecyl ester surfactant samples can be successfully assembled to form nano-sized polymer micelle particles, and the nanoparticles are spherical. With the change of the length of the oligoethylene glycol in the polymer chain, the diameter of the polymer surfactant nanoparticles observed in the TEM field of view gradually increases from 30 nm to 270 nm, and the particle size distribution is uniform. The corresponding DLS test results ( Figure 4 d and Table 6) are in good agreement with the TEM characterization results. This type of long-chain alkyl ester surfactant of phosphorus-containing polymer is a new type of phosphorus-containing polymer surfactant and nanoassembly material, which is expected to be applied in the field of biomedical research.

[0190] 3. Determination of the critical micelle concentration of dodecyl ester surfactants of phosphorus-containing polymers by fluorescence spectroscopy (CMC)

[0191] The critical micelle concentration of the dodecyl ester surfactant of phosphorus-containing polymer in aqueous solution was determined by the pyrene fluorescent probe method. The experimental steps were as follows: first, a 0.012 mg / mL pyrene-acetone solution was prepared; 0.1 mL of the pyrene-acetone solution was added to each of 10 volumetric flasks (10 mL), and the acetone in the volumetric flask was evaporated by heating to ensure that the concentration of the volumetric flask was 6×10 -7 mol / L (saturated solubility of pyrene in aqueous solution at room temperature). Prepare a series of polymer solutions of different concentrations and add them to the aforementioned volumetric flasks to make the solution concentration 0.05μg / mL to 1mg / mL. Place the volumetric flask in a 60℃ water bath and stir for 2h to make pyrene evenly dispersed in the aqueous solution. After cooling to room temperature, add water to make up the volume and then test.

[0192] Pyrene is a highly hydrophobic fluorescent probe with a solubility of 10 -7 M, if there are micelles or other macromolecular systems in the system, pyrene will enter the hydrophobic region of the micelle. As the content of pyrene in the polar solvent changes, the forbidden transition of the first singlet state fluorescence of pyrene changes, and the emission spectrum also shows obvious changes. When the laser wavelength is 394nm, the emission spectrum is usually measured at I 337nm with I334nm The dependence of the intensity ratio on the polymer concentration is determined from the transition point, and its CMC is determined. Table 7 lists the measured critical micelle concentrations of phosphorus-containing polymer dodecyl ester surfactants polyP(EG2)-C12, polyP(EG5)-C12 and polyP(EG7)-C12 in aqueous solution. This type of surfactant has a similar critical micelle concentration to protein-related polysaccharides, including polylactose, polyliposaccharide and polylipomannose (see CG Nanaukwu, Br. Microbiol. Res. J., 2015, 10, 1-9; DKF Santos, Front. Microbiol., 2017, 8, 1-11) biomacromolecule surfactants, and is therefore expected to be used in various fields such as biomedicine and people's daily life toiletries and cosmetics.

[0193] Table 7. Critical micelle concentration of dodecyl ester surfactant solutions of phosphorus-containing polymers

[0194]

[0195] Example 6

[0196] The present invention is used to illustrate the preparation and characterization of phosphorus-containing polymer polyP (Pz) with nitrogen introduced simultaneously.

[0197] According to the initial charging molar ratio of [M(Pz)]0:[HPA]0:[AIBN]0=1:1:0.25, bis(allylpiperazine) M(Pz) (831 mg, 5 mmol), hypophosphorous acid HPA (330 mg, 5 mmol), and AIBN (68 mg, 0.42 mmol) were added to a Shrek bottle filled with ethanol solvent (5 mL), a stirring bar was placed, and the bottle was deoxygenated and passed through an inert gas (argon or nitrogen) three times, and then sealed. Then the Shrek bottle was transferred to a magnetic stirrer set at 1000 rpm and heated in an oil bath (75°C) for polymerization (68 mg of AIBN was added every 24 hours, for a total of three times). After 72 hours of reaction, the mixture was taken out and cooled to room temperature. The sealed container was opened, the polymerization system was diluted with ethanol (5 mL), poured into about 80 mL of petroleum ether, and separated by phase separation in a round-bottomed flask. The upper layer of solvent was removed by decantation, and the remaining small amount of solvent was removed by rotary evaporation. After being thoroughly dried under vacuum at 60°C, a pale yellow solid phosphorus-containing polymer polyP (Pz) was obtained, weighing 856 mg, with a yield of 73.7%. The number average molecular weight of the polymer was 10600 g / mol and the molecular weight polydispersity index was 2.41 by aqueous phase GPC test.

[0198] Example 7

[0199] This example is used to illustrate the polymer flame retardant polyP(Pz)Al and its preparation method.

[0200] The phosphorus-containing polymer polyP (Pz) was prepared according to the proportional scale-up experiment of Example 6. The phosphorus-containing polymer polyP (Pz) (4.645 g, 0.02 mol, calculated as repeating units) was weighed and dissolved in 100 mL of ethanol solvent; aluminum chloride hexahydrate (2.414 g, 0.01 mol) was dissolved in 20 mL of ethanol solvent and slowly added dropwise to the ethanol solution of the phosphorus-containing polymer polyP (Pz) through a constant pressure dropping funnel within 10 min, and reacted at a temperature of 80° C. and a rotation speed of 1000 rpm for 16 h; after the reaction, it was washed with a large amount of ethanol (500 mL) and dried in vacuo at 60° C. to obtain 4.351 g of white powder.

[0201] Example 8

[0202] This example is used to illustrate the polymer flame retardant polyP(Pz)NH4 and its preparation method.

[0203] According to the scaled-up experiment of Example 6, the phosphorus-containing polymer polyP(Pz) was prepared. The phosphorus-containing polymer polyP(Pz) (5 g) was weighed and dissolved in 100 mL of deionized water. At room temperature and a rotation speed of 1000 rpm, a concentrated ammonia solution was slowly added dropwise to the aqueous solution of the phosphorus-containing polymer polyP(Pz) through a constant pressure dropping funnel within 10 min. The pH of the solution was adjusted to pH=10, and the reaction was stirred for 18 h. After the reaction, the solution was rotary evaporated to dryness and vacuum dried at 60°C to obtain 5.31 g of yellow powder.

[0204] Example 9

[0205] This example is used to illustrate a flame retardant polymer composite material containing a polymer flame retardant and its characterization.

[0206] 1. Preparation of flame-retardant polymer composites containing phosphorus-containing polymer flame retardants

[0207] Epoxy resin E-51 (15 g) and polymer flame retardants of different masses, such as the polymer flame retardant polyP(Pz)Al (0.989 g, 5 wt%) prepared in Example 7, were weighed in a 250 mL beaker, and mechanically stirred at 120°C and 500 rpm for 30 min, and then curing agent DDM (3.75 g) was added, and mechanically stirred at 110°C and 500 rpm for 10 min, and then vacuum degassed at 120°C for 3 min to obtain a prepolymer. The prepolymer was poured into a polytetrafluoroethylene mold (size 110 mm × 12 mm × 4 mm, pre-coated with high vacuum silicone grease release agent, and preheated at 120°C), cured at 120°C for 2 h, and then heated to 170°C for 4 h. The obtained specimens are shown in FIG. Figure 5.

[0208] 2. Preparation of Cured Epoxy Resin Control Blank Strips without Addition of Polymer Flame Retardant

[0209] Epoxy resin E-51 (15 g) and curing agent DDM (3.75 g) were weighed in a 250 mL beaker, and mechanically stirred at 110°C and 500 rpm for 30 min, and then vacuum degassed at 120°C for 3 min to obtain a prepolymer. The prepolymer was poured into a polytetrafluoroethylene mold (110 mm × 12 mm × 4 mm in size, pre-coated with high vacuum silicone grease release agent, and preheated at 120°C), cured at 120°C for 2 h, and then heated to 170°C for 4 h. After demolding, a blank control specimen of cured epoxy resin without adding phosphorus-containing polymer flame retardant was obtained. The obtained specimen is shown in FIG. Figure 5 .

[0210] The formula of the cured epoxy resin flame retardant composite material is shown in Table 8.

[0211] Table 8. Cured epoxy resin flame retardant composite material formulation

[0212]

[0213] 3. Thermogravimetric characterization of flame-retardant epoxy resin composites with phosphorus and nitrogen synergistic polymer flame retardants

[0214] The thermal stability of the blank control sample and four groups of epoxy resin flame retardant polymer composite samples in nitrogen atmosphere and air atmosphere was characterized by TGA thermogravimetric analysis. The TGA curves of the blank control and the flame retardant polymer composite are shown in Figure 2. Figure 6 Some typical data are listed in Table 9.

[0215] Table 9. TGA thermogravimetric analysis results of blank control and flame retardant epoxy resin composites

[0216]

[0217] Remark: a Temperature at which 5% decomposition occurs; b The temperature at which the decomposition rate is fastest; c 700℃ decomposition residue.

[0218] Depend on Figure 6 As can be seen from Table 9, in the flame retardant epoxy resin composites with the addition of polymer flame retardant polyP(Pz)Al or polyP(Pz)NH4, the initial decomposition temperature (T d,5% ) and the maximum decomposition rate temperature (T max) is equivalent to that of the blank sample; when 5% of the flame retardant is added, both temperatures are reduced, especially the initial decomposition temperature, which is significantly reduced by more than 20K. At 700℃, the carbon residue (R 700 ) has a higher carbon residue than the blank sample, which is about 8% higher in nitrogen atmosphere and 2-3% higher in air atmosphere. Therefore, the flame retardant polymer composite system retains the high thermal stability of the cured epoxy matrix resin itself and improves its carbonization retention rate in nitrogen atmosphere and air.

[0219] 4. Determination of limiting oxygen index and fire rating of flame retardant epoxy resin composites

[0220] The limiting oxygen index of the blank control and four groups of flame retardant epoxy resin composite specimens in nitrogen atmosphere and air atmosphere was determined, and the fire resistance level was evaluated. The oxygen index of the flame retardant epoxy resin composite was determined according to the national standard GB / T 2406-93 plastic combustion performance test method, and the fire resistance level was measured by the UL94 vertical combustion test. The results are shown in Table 10.

[0221] Table 10. Determination of limiting oxygen index LOI of flame retardant epoxy resin composite and evaluation of fire rating

[0222]

[0223] As shown in Table 10, the LOI of the blank sample is 24.4%, which is a flammable sample (20% to 26%); while the flame retardant epoxy resin composite prepared, the flame retardant sample added with more than 1% polyP (Pz) Al or 1% polyP (Pz) NH4, the LOI of the sample is greater than 26.8%, which is a flame retardant sample (26% to 34%). The results of the UL94 vertical combustion test show that the blank thermosetting sample does not reach the lowest flame retardant level in the UL94 standard during the first combustion, while the thermosetting epoxy resin sample with only 1% polymer flame retardant added reaches the UL94 V-1 level, with a shorter burning time and no dripping. During the secondary ignition, only the blank pure epoxy resin thermosetting sample burned, and the four groups of flame retardant epoxy resin composite samples failed to ignite, indicating that during the first ignition and extinguishing process of the two composite samples, the flame retardant substances released wrapped around the surface of the sample strips, blocking them from secondary combustion and improving the flame retardant performance.

Claims

1. A phosphorus-containing polymer, characterized in that The phosphorus-containing polymer comprises repeating units derived from α,ω-non-conjugated diene monomers and repeating units derived from phosphorus source monomers, wherein the α,ω-non-conjugated diene monomers are selected from bisallyl oligomerized glycol, bisallyl piperazine, bisallyl ether and octadiene, and the phosphorus source monomers are selected from hypophosphorous acid and hypophosphite.

2. The phosphorus-containing polymer according to claim 1, characterized in that The number average molecular weight of the phosphorus-containing polymer is 1000-20000 g / mol, preferably 2000-15000 g / mol; and / or, the molecular weight distribution index Mw / Mn of the phosphorus-containing polymer is 1.1-3.0, preferably 1.2-2.6; And / or, the degree of polymerization of the ethylene glycol unit in the bisallyl oligomerized ethylene glycol is 1-10, preferably 2-7.

3. The phosphorus-containing polymer according to claim 1 or 2, characterized in that The phosphorus-containing polymer is a polymer obtained by gradual polymerization of the α,ω-non-conjugated diene monomer and the phosphorus source monomer via free radical addition.

4. A method for preparing a phosphorus-containing polymer, characterized in that: The preparation method comprises the following steps: In the presence of a free radical initiator, an α,ω-non-conjugated diene monomer and a phosphorus source monomer are subjected to a free radical addition stepwise polymerization reaction, wherein the α,ω-non-conjugated diene monomer is selected from bisallyl oligomerized glycol, bisallyl piperazine, bisallyl ether and octadiene, and the phosphorus source monomer is selected from hypophosphorous acid and hypophosphite.

5. The preparation method according to claim 4, characterized in that: The free radical addition step polymerization reaction is carried out in the presence of a free radical initiator; preferably, the molar ratio of the α,ω-non-conjugated diene monomer, the phosphorus source monomer and the free radical initiator is 1:1:(0.05-0.75), preferably 1:1:(0.2-0.3), for example, 1:1:0.25; and / or, the free radical initiator is selected from azobisisobutyronitrile, dibenzoyl peroxide or persulfate; And / or, the free radical addition step polymerization reaction is carried out in the presence of a solvent; preferably, the solvent is selected from toluene, chlorobenzene, acetonitrile, tetrahydrofuran, 1,4-dioxane, n-propanol, isopropanol, n-butanol, methyl ethyl ketone, ethanol and dimethyl sulfoxide, preferably ethanol; and / or, the volume mass ratio of the solvent to the α,ω-non-conjugated diene monomer is 1.5-5mL:1g, preferably 2-3mL:1g; And / or, the conditions of the free radical addition step polymerization reaction include: temperature 50-100°C, preferably 75±5°C, reaction time 1-80h, preferably 36-72h; and / or, carried out under an inert atmosphere, preferably a nitrogen atmosphere; and / or, stirring speed 500-1500rpm, preferably 1000-1200rpm.

6. A lithium salt complex polyelectrolyte, characterized in that: The lithium salt complex polyelectrolyte comprises the phosphorus-containing polymer according to any one of claims 1 to 3 or the phosphorus-containing polymer prepared by the preparation method according to claim 4 or 5, and doped lithium trifluoromethanesulfonate; Preferably, based on the mass of the lithium salt complex polyelectrolyte, the doping amount of the lithium trifluoromethanesulfonate salt is 0-50wt%, preferably 1-50wt%, more preferably 5-30wt%; Preferably, the α,ω-non-conjugated diene monomer in the phosphorus-containing polymer is bisallyl oligomerized ethylene glycol.

7. A polyphosphonate surfactant, characterized in that The polyphosphonate surfactant comprises a phosphorus-containing polymer according to any one of claims 1 to 3 or a reaction product of a phosphorus-containing polymer prepared by the preparation method according to claim 4 or 5, a catalyst and 1-bromododecane; Preferably, the catalyst is cesium carbonate; Preferably, the α,ω-non-conjugated diene monomer in the phosphorus-containing polymer is bisallyl oligomerized ethylene glycol; Preferably, based on the total repeating units derived from α,ω-non-conjugated diene monomers and phosphorus source monomers in the phosphorus-containing polymer, the molar ratio of the phosphorus-containing polymer, the catalyst and 1-bromododecane is 1:(0.25-2):2, preferably 1:2:

2.

8. Flame retardant based on phosphorus-containing polymers, characterized in that The flame retardant comprises the phosphorus-containing polymer according to any one of claims 1 to 3 or the reaction product of the phosphorus-containing polymer prepared by the preparation method according to claim 4 or 5 and an alkaline substance; Preferably, the α,ω-non-conjugated diene monomer in the phosphorus-containing polymer is bisallylpiperazine; Preferably, the alkaline substance is selected from aluminum chloride and ammonia; Preferably, based on the total repeating units derived from the α,ω-non-conjugated diene monomer and the phosphorus source monomer in the phosphorus-containing polymer, the molar ratio of the phosphorus-containing polymer to the alkaline substance is 1.8-2.2:

1.

9. Flame retardant epoxy resin, characterized in that: The flame retardant epoxy resin comprises a cured epoxy resin and the flame retardant according to claim 8 dispersed therein; Preferably, the flame retardant epoxy resin comprises a reaction product of an epoxy resin, the flame retardant and a curing agent; More preferably, the epoxy resin is E-51; More preferably, the mass ratio of the epoxy resin, the flame retardant and the curing agent is 4:(0.05-0.55):(0.8-1.2), preferably 4:(0.05-0.55):1, and more preferably 4:0.26:1.

Citation Information

Patent Citations

  • Prepn of polyphosphate

    CN100445320C

  • Phosphorus-containing and nitrogen-containing expansion type flame-retardant polymer and preparation method thereof

    CN101914208B

  • Responsive nucleic acid delivery system, preparation method thereof and cross-linked polymer carrier

    CN114984236A

  • Preparation method for polyalkyl hypophosphite

    CN104311712A

  • Preparation method of metal polyalkenyl hypophosphite fire retardant

    CN105949356A